Predicting Water Depth of Lake Using Remote Sensing image - I. Abd-Almajied, Mohammed (Iraqi Journal of Science, 2023)
One of the most important of satellite image is studying the surface wateraccording of its distribution and depth. In this work, three images have been takenfor Baghdad and surrounding for year (1991, 1999 and 2014) and by using of enviprogram has been used. Different classes have been evaluated for Al-Habania andAl-Razaza River according to its depth and water reflectance. In the present workfour types of water depth (very shallow, shallow, moderate, and deep area) havebeen detected.